Assessment of the global financial crisis: special remedies from the shari’ah perspective - Adam Sa'ad, Auwal; Ibrahim, Badruddin; Nurhafiza, Abdul Kadir Malim (2019)
The study investigates some vital courses of the global financial crisis and figured out some important remedies within the context of Shari’ah law. Shari’ah has stipulated market surveillances to ensure strict adherence to the Islamic ethics and trustworthiness in every Shari’ah compatible contractual obligations between individuals and in the public marketplaces.